PERBANDINGAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) DAN INKUIRI - Dini Maielfi, Sisri Wahyuni, (Wahana Sekolah Dasar, 2021)
Effective learning processes have an effect on good learning outcomes. Based on what is observed from student learning outcomes in the teaching and learning process, especially science is still below the minimum completeness level (KKM). This is because the processes that occur in science learning are less meaningful because they have not included students in the process of discovery and generate knowledge from their daily activities, students are not accustomed to solving their own problems and lack of linking teaching materials with students' daily lives. This type of quasi-experimental research with a design from The Static Group Comparison Design is to introduce treatments that are not the same between the two groups ". Then a t-test is performed. Based on the t-test analysis obtained thitung1,398 and ttable = 15. So that it was found that student learning outcomes by applying the CTL model did not differ significantly from students who applied the Inquiry model